1999
DOI: 10.1002/j.1875-595x.1999.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring work stress among Dutch dentists

Abstract: Individual differences among dentists determine to a large degree what is experienced as work stress, but assessment of specific areas is necessary to be able to act preventively. The aim of this study was to develop an instrument to be used to monitor the experience of work stress in detail, to measure its levels, and to relate those levels to job (dis-) satisfaction. A questionnaire was developed, the Dentists' Experienced Work Stress Scale (DEWSS), covering widespread aspects of dental work, which was compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 16 publications
3
28
0
1
Order By: Relevance
“…This scale shows a high degree of reliability and therefore promise for future use in studies of dentists' anxiety and stress. Gorter et al 38 established that there were 49 separate stressors experienced by dentists and Humphris & Cooper identified still more. 39 The items included in the DACSS-R were not simply designed to measure stress-evoking situations, but more specifically, anxiety-provoking situations which had been described as important in prompting changes in clinical decision-making by the participants of the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This scale shows a high degree of reliability and therefore promise for future use in studies of dentists' anxiety and stress. Gorter et al 38 established that there were 49 separate stressors experienced by dentists and Humphris & Cooper identified still more. 39 The items included in the DACSS-R were not simply designed to measure stress-evoking situations, but more specifically, anxiety-provoking situations which had been described as important in prompting changes in clinical decision-making by the participants of the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…2;3 A number of questionnaire-based studies have considered the nature of the stressors present in primary care dental practice. 7 In general, the exploration of dentists' coping 8 has been basic, with generic, trait coping strategies being explored. A single study 9 has found that dentists self-report a perceived inability to cope with many commonly experienced stressors.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the stressors is remarkably consistent across time and country and include work pressure and contents, patient contact, team and financial aspects of practice, career perspectives and the impacts on professional and private lives. 4 A recent national survey of Community Dental Service (CDS) dentists 5 found that stress was related to factors identified by general dental practitioners. It also identified issues relating to poor quality management, administrative duties and staffing levels.…”
Section: Introductionmentioning
confidence: 99%
“…3. the strategies dentists used to cope with the described situations. 4. the effect that dentists believed these emotions had on their clinical decision making.…”
Section: Introductionmentioning
confidence: 99%